4-kW multi-phase battery powered power supply; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Ponomarev A. V.; Korzhenevskiy S. R.; Komarskiy А. A.; Chepusov A. S.; Mamontov Y. I.; Ponomarev S. V. Sergey Viktorovich (High-current electronics, 2017)
Title screen